Immature gastric teratoma in infancy: A case report - Made Walmiky Budi; Fendy Matulatan (Elsevier, 2022)
Introduction: Intra-abdominal mass in neonatal period found in approximately 1 in every 1000 live births. Germ cell tumor, including teratomas account for 9% of intra-abdominal mass in children. Teratoma is defined as germ cell tumor composed of tissue derived from ectoderm, endoderm, and mesoderm. Teratoma has been described in various location. Gastric teratoma is uncommon contributes less than 1% among teratoma in pediatric. The age at presentation occurs principally during infant and young children. Case: A 7-month-old boy referred with chief complain abdominal mass since 2 months ago in upper left abdomen. Within 2 months the mass was getting bigger to size of a coconut. Abdominal examination revealed mass in left hypochondria, 15x12 × 10 cm in size, well defined, irregular surface, mobile, no vena ectasia, and dull in percussion. CT abdomen with contrast showed cystic mass which caused displacement of intraabdominal organs and colon. He was diagnosed with intrabdominal tumor et causa intraabdominal teratoma differential diagnoosis mesenterical cyst. Exploratory laparotomy and tumor excision was performed. Pathologic examination revealed grade III immature teratoma in gastric. Adjuvant chemotherapy was started immediately. Discussion: The most common presentation of gastric teratomas is palpable abdominal mass in epigastrium and left side of the abdomen with abdominal distention. Most of the case was difficult to diagnosed preoperative and complementary studies must be made to confirm diagnosis. The recommended treatment for both mature and immature teratomas is total excision. In case where the alpha-fetoprotein level rising, chemotheraphy is administered.